2021
DOI: 10.1002/hyp.14171
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological management strategies for the control of algal blooms in regulated lowland rivers

Abstract: Reservoirs of lowland floodplain rivers with eutrophic backgrounds cause variations in the hydrological and hydraulic conditions of estuaries and low‐dam reservoir areas, which can promote planktonic algae to proliferate and algal bloom outbreaks. Understanding the ecological effects of variations in hydrological and hydraulic processes in lowland rivers is important for algal bloom control. In this study, the middle and lower reaches of the Han River, China, a typical regulated lowland river with a eutrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…In the context of algal blooms in the Han River, the average air temperature during the 1998 bloom period was 12.5°C. However, as the air temperature dropped below 5°C in mid‐to‐late March, the water temperature in the Han River rapidly dropped, leading to a swift decline in algal blooms (Li et al., 2021). To sum up, the water temperature in the Han River stands as a crucial factor influencing the occurrence of algal blooms in the area.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of algal blooms in the Han River, the average air temperature during the 1998 bloom period was 12.5°C. However, as the air temperature dropped below 5°C in mid‐to‐late March, the water temperature in the Han River rapidly dropped, leading to a swift decline in algal blooms (Li et al., 2021). To sum up, the water temperature in the Han River stands as a crucial factor influencing the occurrence of algal blooms in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al (2021) built a two‐dimensional model to obtain the fitting curves between fish's Weighted Usable Area (WUA) and water levels, and then identified suitable water levels in different periods. To control algal bloom in the middle and lower reaches of Han River, Li, Yin, et al (2021) established a hydrological management framework and determined the threshold flow velocities. The results indicated that differences in river morphology and background nutrient levels could cause significant differences in the critical threshold flow velocities for algal bloom outbreaks.…”
Section: Environmental Flow Calculationmentioning
confidence: 99%
“…Abnormal algal proliferation, which marks the precursor of eutrophication, has been widely studied in low-flow velocity, highdepth water column bodies such as lakes and reservoirs (Zou et al, 2020;Li et al, 2021). A series of achievements have been reported regarding key limiting nutrient factors and ecological control measures in algal proliferation (Cheng et al, 2019;Brookfield et al, 2021).…”
Section: Introductionmentioning
confidence: 99%